Luminescent two-way reversible shape memory polymers prepared by hydroxyl–yne click polymerization. Issue 45 (22nd October 2020) - Wang, Kaojin; Si, Han; Wan, Qing; Wang, Zhiming; Qin, Anjun; Tang, Ben Zhong
Abstract : Luminescent two-way reversible shape memory polymers that could be fabricated into robotic grippers and realize double anti-counterfeiting are prepared via an organobase-catalyzed hydroxyl–yne click polymerization under mild reaction conditions. Abstract : Two-way reversible shape memory polymers (2W-SMPs), capable of changing their shape reversibly, are highly desirable for many potential applications. However, the polymerization reactions used for preparing 2W-SMPs always require harsh conditions, such as metal catalysts, light irradiation and elevated temperature. Furthermore, there are few reports on SMPs that integrated with other functions, such as luminescence. Herein, luminescent 2W-SMPs of semi-crystalline PCL-based networks bearing an aggregation-induced emission (AIE) moiety of tetraphenylethylene (TPE) are designed and prepared via an organobase-catalyzed hydroxyl–yne click polymerization under mild reaction conditions. For comparison, a TPE-free polymer network is also prepared through the same polymerization. The TPE-containing polymer network shows stronger emission than that of the TPE-containing monomer because of the restriction of intramolecular rotation. Both the polymer networks are able to perform excellent reversible shape motions, such as bending–unbending, coiling–uncoiling, and closing–blooming, when they are exposed to cold and warm water. By taking advantage of the shape memory and luminescence properties, the TPE-containing polymer network could be used to construct a luminescent robotic gripper, which can grab and release weights with payload-to-weight ratios much higher than that of many industrial robotic grippers. Moreover, it could also be used to realize a double anti-counterfeiting function. This work represents the first example of luminescent 2W-SMPs, which might be widely applied in diverse areas.